PEMBERIAN GEL (ALOEVERA) TERHADAP STRETCH MARK PADA IBU POST PARTUM - Sridevi, Sridevi; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2024)
According to the International Federation of Obstetricians and Gynecologists, pregnancy is defined as fertilization or the union of sperm and ovum at subsequent nidation or implantation. During pregnancy, a pregnant woman's body experiences physiological changes due to the secretion of the hormones somatomamotropin, estrogen, and progesterone by the placenta. This affects the physiological changes in the entire female reproductive system which can support the development and growth of the fetus in the womb. Especially in dark areas, due to the influence of melanophore-stimulating hormones. The aim of this research was to determine the effect of giving aloe vera gel to post partum mothers. This research method is a type of descriptive research with a case study approach. The sample was 1 post partum mother who was given gel (Aloevera) for stretch marks. By using a measurement observation sheet with OSAS (Observer Scar Assessment Scale). The results of giving Gel (Aloevera) to post partum mothers showed an effect on stretch marks, before giving it a score of 0 (real), after 1 week of treatment there was fading of the stretch marks score 1 (faint), so it can be concluded that giving Gel (Aloevera) effective against stretch marks in post partum mothers